The Correlation Between Students’ Self-Confidence and Their Speaking Skills At Tenth Students Of SMA Muhammadiyah 1 Metro. - Latif, Amirudin; Qomar, Aulia Hanifah; Rumaisah, Febi Faza (Universitas Muhammadiyah Metro, 2024)
Speaking is the ability to communicate in everyday life, and achieving fluency in a specific language is a primary goal in language learning. In the context of speaking, self-confidence stands out as a crucial factor that can either contribute to success or hinder progress in language acquisition. Therefore, the aim of this study was to investigate whether the level of students' self-confidence correlates positively with the speaking skills of tenth-grade students at SMA Muhammadiyah 1 Metro. The research sample consisted of 40 tenth-grade students at SMA Muhammadiyah 1 Metro, selected through purposive sampling. Two types of instruments were employed to collect data from two variables, utilizing questionnaires and a speaking test. In analyzing the data, the researcher correlated the results of the questionnaire with the results of the speaking test using Pearson Product Moment Correlation. The computed result of the correlation coefficient (r count) was 0.194. This value indicates a positive correlation between self-confidence and speaking ability. Specifically, the Pearson correlation places the result within the 0.00–0.20 range, signifying a very low correlation between the two variables. Thus, it suggests that students need to maintain their confidence while also improving their speaking ability to speak fluently and accurately.